Is tryptophan metabolism involved in sleep apnea-related cardiovascular co-morbidities and cancer progression?. Issue 4 (October 2015) - Boulet, L.; Flore, P.; Le Gouellec, A.; Toussaint, B.; Pépin, J.L.; Faure, P.
Abstract Obstructive sleep apnea (OSA) is a multi-component chronic disease affecting 6–17% of adults in the general population. The main hallmark of OSA, intermittent hypoxia (IH), is reported as the main trigger for cardiometabolic co-morbidities. Recent studies, both in rodent models exposed to IH and in humans, have suggested an enhanced incidence and accelerated progression of cancer. However, mechanisms underlying the relationships between OSA and cardiovascular disease on one hand, and cancer on the other hand, have not been entirely deciphered yet. Tryptophan (TRP) metabolism results in nicotinamid and serotonin production, but also in the production of numerous intermediates such as kynurenine, anthranilic and kynurenic acids, 3-hydroxykynurenine, 3-hydroxyanthranilic and quinolinic acids. Each of these metabolites has been linked to cardiovascular disease and cancer mainly in epidemiologic studies. We hypothesize that an alteration of TRP metabolism may play a role in OSA-related cardiovascular co-morbidities and might be one of the players in the relationship between cancer and intermittent hypoxia/OSA. If this is true, interventions aiming to modify TRP metabolism, may constitute a new therapeutic strategy against cardiovascular disease progression and cancer occurrence in OSA populations.